2004
DOI: 10.1016/j.suc.2004.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative ultrasound

Abstract: Intraoperative ultrasound (IOUS) can provide various diagnostic information that is otherwise not available, and can guide or assist various surgical procedures in real time. With refinement of equipment, IOUS is currently used in a wide variety of surgical operations,such as hepatobiliary, pancreatic, endocrine, cardiovascular,and neurologic surgery. Our overview of IOUS, including instrumentation,techniques, indications, advantages, disadvantages,and future perspective, is described in this article. Being sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 84 publications
2
52
0
1
Order By: Relevance
“…IOUS is an essential support in the various intraoperative stages of liver surgery [1]. In our study, 21% of hepatic lesions were identified intraoperatively and in all such cases preoperative surgical strategy was modified.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…IOUS is an essential support in the various intraoperative stages of liver surgery [1]. In our study, 21% of hepatic lesions were identified intraoperatively and in all such cases preoperative surgical strategy was modified.…”
Section: Discussionmentioning
confidence: 62%
“…Intraoperative ultrasonography (IOUS) is the gold standard for staging in primary and secondary metastatic liver tumors [1]. In hepatocellular carcinoma (HCC) IOUS allows detection of new lesions in 7% of cases at the primary hepatectomy and in 7.3% at the secondary hepatectomy [2].…”
Section: Introductionmentioning
confidence: 99%
“…The entire examination is performed with strict observation of standard sterile technique, and the radiologist scrubs and gowns for the exam. There are different options for transducer sterilization [1,5,8] . Ethylene oxide gas with hightemperature aeration of both transducer probe and cord.…”
Section: Techniquementioning
confidence: 99%
“…Most vendors do not recommend it due to potential damage to the equipment. Hydrogen peroxide gas plasma sterilization techniques use low temperature, and are considered safe for use with heat sensitive equipment [1,8] . The turn-around time is about 2 h, enabling use of the probe for more procedures per day.…”
Section: Techniquementioning
confidence: 99%
See 1 more Smart Citation